Opioid Requirement following Arthroscopic Knee Surgery: Are There Predictive Factors Associated with Long-Term Use - Glogovac, Georgina; Kennedy, Mark; Parman, Michael D.; Bowers, Katherine A.; Colosimo, Angelo J.; Grawe, Brian M. (The Journal of Knee Surgery, 2019)
The purpose of this study is to identify patterns of postoperative narcotic use and determine the impact of psychosocial and perioperative factors on postoperative opioid consumption following arthroscopic knee surgery. Fifty consecutive patients undergoing arthroscopic knee surgery were prospectively enrolled. Patients were contacted via telephone at 1 week postoperatively to report their pain level and opioid consumption. The patient was contacted again at 2 weeks, 4 weeks, and 90 days as necessary until opioid cessation, at which time the patient's plan for unused pills was inquired. Opioid consumption was compared using t-tests and one-way analysis of variance for demographic and surgical factors. Linear regression was used to determine whether the Pain Catastrophizing Scale (PCS), Resilience Scale (RS-11), International Knee Documentation Committee questionnaire, or patient-reported pain at 1 week predicted higher opioid consumption. The average morphine equivalent dose of opioid consumption was 142 mg. Sixty-four percent consumed less than 100 mg, and 68% discontinued opioid use by 1 week postoperatively. Seventy-four percent reported surplus pills, and 49% of those patients plans for pill disposal. Factors associated with higher consumption included undergoing a major procedure, having a regional anesthesia block, and higher area deprivation index score (p < 0.05). Higher PCS scores and reported average pain level at 1 week were predictive of higher opioid consumption (p < 0.05). In conclusion, a majority of patients undergoing outpatient knee surgery did not require the entirety of their narcotic prescription. The majority of patients consumed less than 100 mg of morphine equivalents and discontinued opioid use by 1 week postoperatively. Ligament reconstruction, living in an area with a higher index of deprivation, and higher score on the PCS were associated with greater opioid consumption. Overall, patient knowledge regarding opioid disposal was poor, and patients would likely benefit from additional education prior to surgery.
Keywords: opioid consumption; knee arthroscopy; pain catastrophizing; resilience